Are bacterial infections a major cause of cardiovascular disease? - Kissinger, Dohn (Frontiers in Cardiovascular Medicine, 2024)
The Cholesterol Theory is the prevailing theory of cardiovascular disease (CVD). It proposes that CVD is caused by high levels of Low-Density Lipoprotein Cholesterol (LDL-C}, the so-called "bad cholesterol". The LDL-C particles are assumed to burrow into the arterial walls and damage them, leaving behind plaques that narrow the blood vessels and result in heart attacks and strokes. We list several examples that show that LDL-C is not the cause of CVD. We then examined if bacterial infections are a major cause of CVD.